The Influence of Net Profit Margin, Return on Asset, Debt to Equity Ratio, and Current Ratio on Stock Prices in Manufacturing Companies in the Basic and Chemical Industries Listed on the Indonesia Stock Exchange in 2019-2021. - warta Simamora, Rina; Angelia, Nia; Syahputra, Oky (Akuntansi Prima, 2025)
This research aims to examine the influence of NPM, ROA, capital structure and CR on share prices in manufacturing companies in the basic industrial and chemical sectors listed on the IDX. The sample used was 28 companies out of 73 companies listed during the 2019-2022 period. The analysis used is multiple linear regression analysis with SPSS application tools. From the statistical tests carried out, it was found that ROA partially had a significant positive effect on share prices, NPM and capital structure partially had no significant effect on share prices, CR partially had a significant negative effect on share prices. Meanwhile, simultaneously NPM, ROA, capital structure and CR have a significant effect on stock prices listed on the IDX.